ANALISIS FAKTOR-FAKTOR DAYA TARIK KEMASAN GULA MERAH TERHADAP MINAT PEMBELIAN ULANG KONSUMEN - Sumrotul Hoiriyah; Banun Diyah Probowati; Umi Purwandari (AGROINTEK, 2015)
Brown sugar is human’s daily need that tends to increasingly change. The brown sugar is produced in Sumenep and delivered widely to Sampang region and surrounds it. The brown sugar sold in market is usally unpackaged brown sugar or not yet packaged. Packaging is important to increase the value of brown sugar itself. Factors exist in packaging is color, design, shape, size, physical material and information written on the label. The purpose of this study is to determine the amount influence of packaging factors on re-purchasing interest by applying multiple linear regressions analysis method. The result states that the color of package influences the increasing of re-purchasing interest of 0,714, packaging design influences the increasing of re-purchasing interest of 0,171, physical material influences the increasing of re-purchasing interest of 0,473, information writer on a label influences the increasing of re-purchasing interest of 0,409, shape influences the increasing of re-purchasing interest of -0,219 and size influences the increasing of re-purchasing interest of -0,047. So, the dominant factors are color, design, physical material and information written on a label.